Constitution making during state building - Wallis, Joanne (Cambridge : Cambridge University Press, 2014)
How can fragmented, divided societies that are not immediately compatible with centralised statehood best adjust to state structures? This book employs both comparative constitutional law and comparative politics, as it proposes the idea of a'constituent process', whereby public participation in constitution making plays a positive role in state building. This can help to foster a sense of political community and produce a constitution that enhances the legitimacy and effectiveness of state institutions because a liberal-local hybrid can emerge to balance international liberal practices with local customary ones. This book represents a sustained attempt to examine the role that public participation has played during state building and the consequences it has had for the performance of the state. It is also the first attempt to conduct a detailed empirical study of the role played by the liberal-local-hybrid approach in state building.
Part I. Normative Justification for a Constituent Process -- The normative justification -- A constituent process -- Part II. Minimal Participation in Timor-Leste -- State building and constitution making in Timor-Leste -- Constituent power in Timor-Leste -- Constituted power in Timor-Leste -- Part III. Extensive Participation in Bougainville -- State building and constitution making in Bougainville -- Constituent power in Bougainville -- Constituted power in Bougainville -- Part IV. Comparing the two cases and conclusions -- Comparing the constitution-making processes -- The role of a constituent process in state building.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Constitutional law -- Timor-Leste.; Constitutional law -- Papua New Guinea -- Bougainville Island; Political participation -- Timor-Leste.; Political participation -- Papua New Guinea -- Bougainville Island; Constituent power -- Timor-Leste.; Constituent power -- Papua New Guinea -- Bougainville Island; Representative government and representation -- Timor-Leste.; Representative government and representation -- Papua New Guinea -- Bougainville Island